2023
DOI: 10.1002/slct.202203310
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonal SnO2 Nanoparticles: An Efficient Photocatalyst for the Degradation of Hazardous Ionic Dyes

Abstract: An elegant approach was made to synthesize tetragonal shape SnO2 nanoparticles using solution combustion method and subjected to various characterization (X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), UV‐Vis diffuse reflectance spectroscopy (UV‐DRS), Photoluminescence (PL) spectroscopy, Raman spectra, thermogravimetric analysis (TGA), differential thermal analysis (DTA), X‐ray photoelectron spectrometer (XPS), N2 adsorption‐desorption isotherms (BET), liquid chromatography with mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Consequently, the results showed that ˙OH > O 2 ˙ − > h˙ + . 28 Degradation-causing radicals were uncovered through research into the mechanism of the photocatalytic reaction. By exposing the photocatalyst to sunlight, holes are created in the valence band, and e − are created in the conduction band, transitioning the material from a semiconductor to an electrical conductor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the results showed that ˙OH > O 2 ˙ − > h˙ + . 28 Degradation-causing radicals were uncovered through research into the mechanism of the photocatalytic reaction. By exposing the photocatalyst to sunlight, holes are created in the valence band, and e − are created in the conduction band, transitioning the material from a semiconductor to an electrical conductor.…”
Section: Resultsmentioning
confidence: 99%
“…27 Rhodamine B is a cationic dye that causes hormonal imbalance and apoptosis in hypothalamic cells in acute exposure. 28 Moreover, degradation studies of brilliant green dye and rhodamine B dye were carried out using as-synthesized nanomaterials (a-FeOOH and a-Fe 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis using nanoparticles (NPs) is a promising method for dye removal from water due to their exceptional and highly tunable surface properties compared to bulk materials. NPs offer a wider scope in catalytic processes thanks to their unique surface characteristics, and they have higher diffusion rates coupled with lower reinforcing capabilities, all of which collectively enhance their catalytic performance [8,9,19,20]. Like, the potential of rGO-250 as a robust photocatalyst for dye degradation, highlighting its adaptability and efficiency in well-defined circumstances that require pH, dye concentration, catalyst dosage, and recyclability into consideration.…”
Section: Catalyst Dosage and Pollutant Degradationmentioning
confidence: 99%
“…TiO 2 and ZnO nanopowder particularly recently are used as efficient, inexpensive, and nontoxic semiconductor photocatalysts for the degradation of a variety of organic pollutants. [23] Various photocatalysts in different forms such as nanoparticles, nanofibers, and nanorods have been studied to enhance photocatalytic activity [24][25][26][27] since dyes cannot be effectively degraded without a suitable photocatalyst. [28][29][30] The utilization of ZnO in photocatalysis has gained significant interest compared to commonly used TiO 2 due to its catalytic activity and quantum performance.…”
Section: Introductionmentioning
confidence: 99%